Bioluminescence of Pseudomonas fluorescens HK44 in the course of encapsulation into silica gel. Effect of methanol - Trögl, Josef; Kuncová, Gabriela; Kuráň, Pavel (Folia microbiologica, 2010)
The bioluminescence (BLM) and colony-forming units (CFU) of Pseudomonas fluorescens HK44 were monitored during encapsulation into pre-polymerized Si(OMe)₄. The non-induced BLM of free cells was increased in the presence of 0.5-2.5 % MeOH. After mixing silica sol with the cell suspension, both BLM and CFU dropped to 1-3 and 8-18 %, respectively; both remained lowered as long as the silica biofilm contained residual MeOH. The kinetics of MeOH being released from silica biofilms (a thickness of 2-6 mm) were first-order. The decrease of bacterial activity due to encapsulation was proportional to the biofilm thickness. MeOH evolving during encapsulation is probably the principal stress factor but not the only one.
Keywords: financování organizované; methanol; Silica Gel; Financing, Organized; luminiscence; Pseudomonas fluorescens; Luminescence; Methanol; mikrobiální viabilita; Microbial Viability; silikagel